PERSEPSI DAN RESPONS PERILAKU PEMUDA TERHADAP HIV/AIDS: STUDI KUANTITATIF PADA MAHASISWA DI INDONESIA - Cindy Israeni Ansar; Afni Amirudin (Indonesian Journal of Social Science and Education (IJOSSE), 2025)
Despite decades of global HIV/AIDS education efforts, the gap between awareness and preventive behavior among youth remains a persistent challenge. University students—typically well-educated and socially engaged—are expected to be proactive in health matters, yet many remain passive in HIV prevention efforts. This study examines the knowledge, attitudes, and behaviors of university students in Indonesia regarding HIV/AIDS, and analyzes the cognitive and structural barriers that hinder behavioral change. The research applies two theoretical frameworks: the Theory of Planned Behavior (TPB) and the Health Belief Model (HBM). A quantitative survey was conducted among 268 students at Hasanuddin University. Descriptive and inferential statistics were used to assess levels of HIV/AIDS knowledge, attitudes, and preventive actions. Skewness and kurtosis were also calculated to explore distributional patterns. While students demonstrated high levels of knowledge (M = 16.34) and positive attitudes (M = 31.36), their preventive behavior was notably low (M = 10.74), with skewed distributions indicating widespread inaction. Misconceptions about HIV transmission and curability were common. Both TPB and HBM helped explain the role of perceived barriers, weak normative support, and low self-efficacy in limiting behavioral intention. Findings highlight a critical knowledge–action gap driven by social stigma, misinformation, and lack of institutional cues to action. Effective HIV prevention requires not only awareness but also structured interventions that enhance agency, normalize testing, and dismantle behavioral barriers within youth populations